Polyvinyl alcohol hydrogel and preparation method thereof
By adding borax and biomass carbon quantum dots to polyvinyl alcohol to form a cross-linked network, the biodegradability and mechanical strength problems of the self-healing hydrogel were solved, and an efficient self-healing conductive hydrogel suitable for bioengineering was prepared.
Patent Information
- Application Number
- CN202510954963.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-09-23
AI Technical Summary
Existing self-healing hydrogels have poor biodegradability, low mechanical strength and certain toxicity, which limits their application in the field of bioengineering.
By adding borax to polyvinyl alcohol (PVA) to generate a borate cross-linked network, and modifying it with biomass carbon quantum dots, a polyvinyl alcohol/carbon quantum dot/borax hydrogel was formed, and the freeze-thaw method was combined to improve the self-healing efficiency and mechanical properties of the material.
The prepared self-healing conductive hydrogel has good biocompatibility, mechanical properties and self-healing ability, and is suitable for the field of bioengineering.
Smart Images

Figure CN120682495A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogels, and particularly relates to a polyvinyl alcohol hydrogel and a preparation method thereof. Background Art
[0002] Hydrogels are soft materials composed of hydrophilic polymers formed through chemical or physical crosslinking to form a network-like structure. They possess certain self-healing properties, namely the ability of polymer molecules to reorganize and rebuild themselves upon bond breakage. Self-healing hydrogels have potential applications in bioengineering, such as drug delivery systems, wound dressings, electronic skin, and wearable flexible devices. Despite rapid development, challenges such as poor biodegradability, low mechanical strength, and a certain degree of toxicity have limited their further development. Therefore, the development and preparation of environmentally friendly, biocompatible, and multifunctional self-healing hydrogels has attracted widespread research attention. Polyvinyl alcohol (PVA) is non-toxic, exhibits good biocompatibility, and exhibits excellent mechanical properties. However, conventional PVA hydrogels are prone to breakage in dehydrated conditions during practical applications. To achieve this goal, this patent proposes a method to enhance the hydrogel's self-healing ability by adding borax (Na2B4O7·10H2O) to PVA to form borate, which crosslinks the polymer network. This crosslinked network locks water within the hydrogel, reducing water evaporation and enhancing its mechanical properties. However, polyvinyl alcohol-borax hydrogels still have many shortcomings, such as fragility and low healing efficiency. This patent modifies polyvinyl alcohol / borax hydrogels with highly biocompatible nanocarbon quantum dots to form polyvinyl alcohol / carbon quantum dot / borax hydrogels. The carbon quantum dots' multiple carbonyl and amino groups and large π-conjugated electron structure enhance the composite's hydrogen bonding and van der Waals forces, achieving improved self-healing efficiency while also maintaining electrical conductivity. A freeze-thaw method is then used to further enhance the material's strength. Summary of the Invention
[0003] In view of the deficiencies of the prior art, the present invention provides a polyvinyl alcohol hydrogel and a preparation method thereof to solve the problems of poor biodegradability, low mechanical strength and toxicity of existing self-healing materials.
[0004] The technical solution provided by the present invention is as follows:
[0005] The present invention provides a method for preparing a polyvinyl alcohol hydrogel, comprising the following steps: Mixing polyvinyl alcohol, biomass carbon quantum dot solution, plasticizer and first cross-linking agent, and heating and dissolving to form a homogeneous solution; The homogenized solution is defoamed and injected into a mold, and subjected to freeze-thaw cycles to form a primary hydrogel; Immersing the primary hydrogel in a solution containing a second cross-linking agent for secondary cross-linking to obtain a composite polyvinyl alcohol hydrogel; The biomass carbon quantum dot solution is prepared by hydrothermal reaction of biomass raw materials.
[0006] Furthermore, the method for preparing the biomass carbon quantum dot aqueous solution includes: Biomass powder, nitric acid and water are added to a polytetrafluoroethylene reactor for hydrothermal reaction. After the reaction is completed, the solution is cooled to room temperature, centrifuged and filtered to obtain the biomass carbon quantum dot solution; wherein the biomass powder is wheat straw powder.
[0007] Furthermore, the mass volume ratio of the biomass powder and nitric acid is 0.1-0.5 g: 0-0.5 mL.
[0008] Furthermore, the temperature of the hydrothermal reaction is 200-250° C., and the reaction time is 3-7 h.
[0009] Furthermore, the plasticizer is glycerol, and the mass ratio of the polyvinyl alcohol, the biomass carbon quantum dot solution and the glycerol is 1:3~6:2.
[0010] Furthermore, the first cross-linking agent is borax, and the added amount of the borax is 10-20% of the mass of the polyvinyl alcohol.
[0011] Furthermore, the solution containing the second cross-linking agent is a calcium chloride aqueous solution, the concentration of the calcium chloride aqueous solution is 5-15 wt %, and the secondary cross-linking time is 8-24 h.
[0012] Furthermore, the heating and dissolving is performed by heating the mixture to 90-95° C. in a constant temperature magnetic water bath and stirring for 2-4 hours, and the defoaming is performed by ultrasonic treatment with an ultrasonic power of 200-300 W and a treatment time of 2-40 minutes.
[0013] Furthermore, the freeze-thaw cycle treatment includes: freezing at -16~-20°C for 22~26 hours, followed by thawing at 2~4°C for 10~14 hours, with the number of cycles being ≥1.
[0014] The present invention also provides a polyvinyl alcohol hydrogel prepared according to the above-mentioned preparation method.
[0015] Beneficial effects
[0016] The present invention uses recycled biomass as a carbon source to prepare carbon quantum dots, which has low cost, simple operation, energy conservation and emission reduction, reduces its pollution to the environment, realizes resource utilization and "dual carbon" development, and generates greater economic and social benefits.
[0017] This study uses polyvinyl alcohol as a backbone to prepare a hydrogel, using borax or calcium chloride as a crosslinker and carbon quantum dots to modify it. The result is a novel self-healing, conductive hydrogel with excellent biodegradability and biocompatibility. The resulting self-healing conductive hydrogel exhibits excellent mechanical properties, electrical conductivity, and self-healing properties, suggesting promising applications.
[0018] The present invention generates borate by adding borax to PVA, causing cross-linking of the polymer network structure, thereby enhancing the self-healing ability of the hydrogel, locking water in the cross-linked network, reducing water volatilization, and enhancing its mechanical properties.
[0019] This invention modifies a polyvinyl alcohol / borax hydrogel with highly biocompatible nanocarbon quantum dots to create a polyvinyl alcohol / carbon quantum dot / borax hydrogel. The carbon quantum dots' multiple carbonyl and amino groups and large π-conjugated electron structure enhance the composite's hydrogen bonding and van der Waals forces, improving its self-healing efficiency while also maintaining electrical conductivity. A freeze-thaw method is then used to further enhance the material's strength.
[0020] The self-healing conductive hydrogel prepared by the invention has good mechanical properties, electrical conductivity and self-healing properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Fluorescence spectra of carbon quantum dots prepared in Examples 1 to 5 with different amounts of wheat straw;
[0022] Figure 2 Fluorescence spectra of carbon quantum dots prepared at different reaction temperatures in Example 1, Example 6, and Example 7;
[0023] Figure 3 Fluorescence spectra of carbon quantum dots at different reaction times in Example 1 and Example 8 to Example 11;
[0024] Figure 4 Fluorescence spectra of carbon quantum dots with different nitric acid addition amounts in Example 1 and Example 12 to Example 16;
[0025] Figure 5 The rheological diagrams of hydrogels with different ingredient ratios;
[0026] Figure 6 is the self-healing diagram of PVA-4 hydrogel;
[0027] Figure 7 The conductivity diagram of PVA-4 hydrogel. DETAILED DESCRIPTION
[0028] The following examples are provided to further illustrate the present invention, but are not intended to limit the present invention. The technical solution is described clearly and completely below in conjunction with the accompanying drawings and examples. It is apparent that the described embodiments are only a portion of the present invention, not all of the embodiments. All other embodiments obtained by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are intended to fall within the scope of protection of the present invention.
[0029] The wheat straw powder used in the following examples was obtained from farmland around Xuzhou. After cleaning, it was dried in a forced air drying oven to constant weight, ground into fine powder using a grinder, passed through a 60-mesh sieve, and bottled and sealed for later use.
[0030] Example 1: Preparation method of wheat straw carbon quantum dot solution
[0031] Weigh 0.2 g of wheat straw powder and pour it into a polytetrafluoroethylene reactor. Add 10 mL of deionized water, set the oven temperature to 200 °C, and set the time to 5 h. After the reaction is completed, cool the reactor to room temperature and centrifuge it at 4000 r / min for 2 min. After centrifugation, pour the upper liquid into a syringe equipped with a 0.22 μm filter for filtration. The filtrate is dripped into a dialysis bag with a molecular weight cutoff of 1000 Daltons, and then the dialysis bag is placed in 250 mL of deionized water for dialyzation for 24 h to obtain a carbon quantum dot solution.
[0032] Example 2
[0033] The difference between this embodiment and embodiment 1 is that the amount of wheat straw powder is 0.1 g.
[0034] Example 3
[0035] The difference between this embodiment and embodiment 1 is that the amount of wheat straw powder is 0.3 g.
[0036] Example 4
[0037] The difference between this embodiment and embodiment 1 is that the amount of wheat straw powder is 0.4 g.
[0038] Example 5
[0039] The difference between this embodiment and embodiment 1 is that the amount of wheat straw powder is 0.5 g.
[0040] Example 6
[0041] The difference between this embodiment and embodiment 1 is that the temperature is 150°C.
[0042] Example 7
[0043] The difference between this embodiment and embodiment 1 is that the temperature is 250°C.
[0044] Example 8
[0045] The difference between this embodiment and embodiment 1 is that the reaction time is 1 h.
[0046] Example 9
[0047] The difference between this embodiment and embodiment 1 is that the reaction time is 3 h.
[0048] Example 10
[0049] The difference between this embodiment and embodiment 1 is that the reaction time is 7 h.
[0050] Example 11
[0051] The difference between this embodiment and embodiment 1 is that the reaction time is 9 h.
[0052] Example 12
[0053] This embodiment differs from embodiment 1 in that 0.1 mL of concentrated nitric acid is added.
[0054] Example 13
[0055] This embodiment differs from embodiment 1 in that 0.2 mL of concentrated nitric acid is added.
[0056] Example 14
[0057] This embodiment differs from embodiment 1 in that 0.3 mL of concentrated nitric acid is added.
[0058] Example 15
[0059] This embodiment differs from embodiment 1 in that 0.4 mL of concentrated nitric acid is added.
[0060] Example 16
[0061] This embodiment differs from embodiment 1 in that 0.5 mL of concentrated nitric acid is added.
[0062] Figure 1 Fluorescence spectra of carbon quantum dots prepared in Examples 1 to 5 using different amounts of wheat straw. When the amount of wheat straw powder increased from 0.1 g to 0.2 g, the fluorescence intensity increased by approximately 20%. Further increases in the amount of wheat straw resulted in a significant decrease in fluorescence intensity, reaching its lowest level at 0.5 g. This is likely due to the strong water absorption of wheat straw powder, which hindered its dispersion in the solvent. Therefore, the optimal amount of wheat straw was 0.2 g / 10 mL of deionized water.
[0063] Figure 2The fluorescence spectra of carbon quantum dots prepared at different reaction temperatures in Examples 1, 6, and 7 are shown. The figure shows that the fluorescence intensity of the carbon quantum dots synthesized at 150°C is very low, suggesting that it is difficult to decompose the large straw molecules into small carbon quantum dots at this temperature. The synthesis temperature of the carbon quantum dots is reached only after the temperature reaches 200°C, and the fluorescence intensity reaches its maximum at 250°C.
[0064] Figure 3 The fluorescence spectra of the carbon quantum dots obtained at different reaction times for Examples 1, 8, and 11 are shown. As the reaction time increases from 1 to 3 hours, the fluorescence intensity of the carbon quantum dots increases dramatically, reaching its peak at 3 hours. With further reaction time, the fluorescence intensity decreases slightly but remains stable. This is presumably due to the uneven size of the carbon quantum dots. Therefore, 5 hours is the optimal reaction time.
[0065] Figure 4 Fluorescence spectra of carbon quantum dots at different nitric acid dosages, as shown in Examples 1 and 12-16. The figure shows that the fluorescence intensity increases tenfold with increasing nitric acid dosage from 0.1 mL to 0.3 mL. Further increases in nitric acid concentration lead to a decrease in fluorescence intensity and a gradual stabilization. The fluorescence effect is optimal when the nitric acid dosage is 0.3 mL.
[0066] Example 17: Preparation of self-healing hydrogel Weigh 3 g of polyvinyl alcohol (degree of polymerization 1750) and place it in a three-necked flask. Add 17 mL of deionized water and 6 g of propylene glycol, and swell it at room temperature for 3 h. Use a constant temperature magnetic water bath to heat to 95 °C and stir for 3 h to fully dissolve the polyvinyl alcohol. Then, transfer the solution into a mold while it is hot, place it in an ultrasonic cleaner and sonicate for 30 min to remove bubbles. After leaving it at room temperature for 12 hours, transfer it to a refrigerator and freeze it at -16 °C for 24 h to freeze and crystallize it. Then place it in a 3 °C refrigerator for 12 h. Perform a freeze-thaw operation to crystallize the polyvinyl alcohol to form a hydrogel, and obtain sample PVA-1.
[0067] Example 18
[0068] The operation steps of this example are the same as those of Example 17, except that 0.3 g of borax is added to obtain sample PVA-2.
[0069] Example 19
[0070] The operation steps of this example are the same as those of Example 17, except that 0.6 g of borax is added to obtain sample PVA-3.
[0071] Example 20
[0072] The operating steps of this example are the same as those of Example 17, except that 17 mL of water is replaced with the N-doped carbon quantum dot aqueous solution prepared in Example 14 and 0.6 g of borax is added to obtain sample PVA-4.
[0073] Example 21
[0074] 100 mg of methylene blue was added to the hydrogel obtained in Example 20 for staining to obtain sample PVA-5.
[0075] Example 22
[0076] The operating steps of this example are the same as those of Example 20, except that the hydrogel is immersed in a 10 wt % calcium chloride aqueous solution for 12 h to obtain sample PVA-6.
[0077] Tensile properties were tested on five groups of specimens with a width of 10 mm, a thickness of 4.5 mm, and a cross-sectional area of 45 mm. 2 , the specimen gauge length is set to 20 mm, and the tensile properties test results are shown in Table 1:
[0078] Table 1 Tensile properties test results
[0079]
[0080] From the data in Table 1, it can be seen that the tensile strength (destructive load) of pure PVA hydrogel is the lowest, but the elongation at break is high, which shows that it has good toughness. When borax is added to the system, the tensile strength is improved and the elongation at break is reduced. When the mass of borax is 20% of the mass of PVA, the tensile strength is greatly improved and the elongation at break is maintained. This shows that borax as a cross-linking agent can well form an associated OBO bond with the vicinal diol hydroxyl groups between the polyvinyl alcohol molecular chains, thereby enhancing the interaction force between the molecular chains. Macroscopically, the tensile strength is greatly improved. When carbon quantum dots are introduced into the system, the non-covalent bond effects such as the van der Waals force and π-π stacking effect in the system are enhanced. Although not as good as the covalent bond effect, it can also slightly improve the tensile strength and elongation at break. When Ca is introduced into the PVA hydrogel, the tensile strength and elongation at break are greatly improved. 2+ Afterwards, Ca 2+ It forms ionic bond interactions with PVA hydroxyl groups, further cross-linking the PVA network structure to form a double network cross-linking structure, which greatly improves the tensile strength and elongation at break.
[0081] Figure 5 The relationship between the storage modulus and loss modulus of the five hydrogels at different rotational speeds is shown in the figure. As can be seen from the figure, for PVA hydrogel, when the rotational speed ω is less than 350 rad / s, the elastic modulus G ’ Greater than the loss modulus G ”, the material mainly undergoes elastic deformation, the hydrogel is in solid state, and has a good and stable network structure. ’ Equal to the loss modulus G ” When the rotation speed ω is greater than 350 rad / s, the loss modulus G of the hydrogel ” It increases with the increase of rotation speed and far exceeds the elastic modulus G ’ , the hydrogel mainly undergoes viscous deformation. From the elastic modulus G of the composite hydrogel ’ It can be observed that the addition of borax to PVA hydrogel increases the elastic modulus to 2×10 3 pa, which enhances the strength of the gel.
[0082] Figure 6 The self-healing of PVA-4 hydrogel after 24 hours of cutting was tested. Its mechanical properties showed that the failure load was 7.773 N, the fracture deformation was 8.71 mm, and the elongation at break was 43.55%. The tensile strength decreased by 47.05% compared with before fracture, and the elongation at break decreased by 74%.
[0083] Figure 7 The conductivity of PVA-4 hydrogel is shown in Figure 2. All the prepared hydrogel samples are conductive and can make diodes emit light. The hydrogel with carbon quantum dot solution has better conductivity than other hydrogels.
[0084] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with this technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a polyvinyl alcohol hydrogel, characterized in that: The following steps are involved: Mixing polyvinyl alcohol, biomass carbon quantum dot solution, plasticizer and first cross-linking agent, and heating and dissolving to form a homogeneous solution; The homogenized solution is degassed and injected into a mold, and subjected to freeze-thaw cycles to form a primary hydrogel; Immersing the primary hydrogel in a solution containing a second crosslinking agent for secondary crosslinking to obtain a composite polyvinyl alcohol hydrogel; The biomass carbon quantum dot solution is prepared by hydrothermal reaction of biomass raw materials.
2. The method for preparing polyvinyl alcohol hydrogel according to claim 1, wherein The preparation method of the biomass carbon quantum dot aqueous solution comprises: Biomass powder, nitric acid and water are added to a polytetrafluoroethylene reactor for hydrothermal reaction. After the reaction is completed, the solution is cooled to room temperature, centrifuged and filtered to obtain the biomass carbon quantum dot solution; wherein the biomass powder is wheat straw powder.
3. The method for preparing the polyvinyl alcohol hydrogel according to claim 2, wherein: The mass volume ratio of the biomass powder and nitric acid is 0.1-0.5 g: 0-0.5 mL.
4. The method for preparing the polyvinyl alcohol hydrogel according to claim 2, wherein: The temperature of the hydrothermal reaction is 200-250° C., and the reaction time is 3-7 h.
5. The method for preparing polyvinyl alcohol hydrogel according to claim 1, wherein The plasticizer is glycerol, and the mass ratio of the polyvinyl alcohol, the biomass carbon quantum dot solution and the glycerol is 1:3-6:
2.
6. The method for preparing polyvinyl alcohol hydrogel according to claim 1, characterized in that: The first cross-linking agent is borax, and the added amount of the borax is 10-20% of the mass of the polyvinyl alcohol.
7. The method for preparing polyvinyl alcohol hydrogel according to claim 1, characterized in that: The solution containing the second cross-linking agent is a calcium chloride aqueous solution, the concentration of the calcium chloride aqueous solution is 5-15 wt %, and the secondary cross-linking time is 8-24 hours.
8. The method for preparing polyvinyl alcohol hydrogel according to claim 1, characterized in that: The heating dissolution is performed by heating to 90-95° C. in a constant temperature magnetic water bath and stirring for 2-4 hours. The defoaming is performed by ultrasonic treatment with an ultrasonic power of 200-300 W and a treatment time of 2-40 minutes.
9. The method for preparing polyvinyl alcohol hydrogel according to claim 1, wherein: The freeze-thaw cycle treatment includes: freezing at -16~-20°C for 22~26 hours, followed by thawing at 2~4°C for 10~14 hours, with the number of cycles being ≥1.
10. A polyvinyl alcohol hydrogel, characterized in that Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method and application of carbon quantum dot-doped polyvinyl alcohol-based hydrogel
CN121895597A